Multimedia Development to Promote Cultural Tourism in Phra Nakhon District, Bangkok - Sangsawang, Anumas; Daengmak, Sravudh; Asampinpongs, Viranpatch (Journal of Engineering and Industrial Technology, Kalasin University, 2025)
This research aimed to 1) develop multimedia to promote cultural tourism in Phra Nakhon District, Bangkok, 2) evaluate multimedia efficiency, and 3) evaluate multimedia satisfaction in promoting cultural tourism. This research applied both quantitative and qualitative approaches. The samples were divided into two groups, that is, 5 experts selected by the purposive sampling and 30 general users. The research tools consisted of 1) promote cultural tourism in Phra Nakhon District, Bangkok, 2) evaluation form of multimedia efficiency, and 3) questionnaire on user satisfaction on multimedia in promoting cultural tourism. The results obtained multimedia to promote cultural tourism in Phra Nakhon District, Bangkok in the form of tourism e-Book. The evaluation result from the experts was at a high level ( = 4.69, S.D.= 0.49). The overall result of user satisfaction on multimedia obtained from general users was at a high level ( = 4.51, S.D. = 0.47). It could be concluded that the developed multimedia could enhance experiences in tourism and promote cultural values in Phra Nakhon District, Bangkok very well. Moreover, it could be applied as a model for multimedia development in further promoting tourism in other aspects.